Tuan Guru’s role in social media to prevent the spread of Covid-19 virus in west Nusa Tenggara, Indonesia - AMY, NAJAMUDDIN; WIJOYO, SUPARTO (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT The first positive case of COVID-19 in West Nusa Tenggara occurred in April 2020. The study aims to analyze the role of religious leaders in providing understanding to the community. A qualitative method with a phenomenological approach is used to illustrate the role of the Tuan Guru in COVID-19 prevention through social media. The results indicate that until now Tuan Guru has been an important partner for the government. The role of Tuan Guru in preventing COVID-19 can be seen from the activities on social media. Further discussion indicates that Tuan Guru’s role has a significant influence on community perceptions in the prevention of COVID-19. RESUMEN El primer caso positivo de COVID-19 en West Nusa Tenggara ocurrió en abril de 2020. El estudio tiene como objetivo analizar el papel de los líderes religiosos en brindar comprensión a la comunidad. Se utiliza un método cualitativo con enfoque fenomenológico para ilustrar el papel del Tuan Guru en la prevención de COVID-19 a través de las redes sociales. Los resultados indican que hasta ahora Tuan Guru ha sido un socio importante para el gobierno. El papel del mismo en la prevención de COVID-19 se puede ver en las actividades en las redes sociales. Una discusión adicional indica que su papel tiene una influencia significativa en las percepciones de la comunidad en la prevención de COVID-19.